Human bone marrow contains a subset of quiescent early memory CD8+ T cells characterized by high CD127 expression and efflux capacity. Issue 12 (27th October 2014) - Kudernatsch, Robert F.; Letsch, Anne; Guerreiro, Manuel; Löbel, Madlen; Bauer, Sandra; Volk, Hans‐Dieter; Scheibenbogen, Carmen
Abstract : Even today it is still not completely understood how CD8 + T‐cell memory is maintained long term. Since bone marrow (BM) is a niche for immunological memory, we sought to identify long‐lasting early memory CD8 + T cells in this compartment. To achieve this, we looked for CD8 + T cells that are able to efflux Rhodamine 123, a typical property of stem cells. Indeed, we identified a distinct subset of CD8 + T cells in BM, with the capacity to efflux and high CD127 expression. These CD127 hi effluxers are conventional CD8 + T cells exhibiting a broad TCR‐Vβ repertoire and are generated in response to viral peptides in vitro. CD127 hi effluxer CD8 + T cells have an early memory phenotype defined by preferential TNF‐α production and a Bcl‐2 hi, KLRG‐1 low profile. This population has long telomeres and shows constitutively low frequencies of Ki‐67 expression ex vivo, but has a high proliferative and differentiation capacity in vitro. However, IL‐15 downmodulates CD127 in CD127 hi effluxer CD8 + T cells in vitro. Consequently, the CD127 low effluxer subset may comprise cells recently exposed to IL‐15. Taken together, CD127 hi effluxer CD8 + T cells represent a novel population of early memory T cells resident in BM with properties required for long‐lived memory.